Diamagnetic Susceptibility of a Magneto-Donor in GaAs Spherical and Cylindrical Quantum Dot - Edrissi, S. Janati.; Zorkani, I.; Rahmani, K.; Jorio, A. (Advanced Aspects of Engineering Research Vol. 2, 2021)
The form effect on the binding energy and diamagnetic susceptibility of a shallow donor confined to move in Quantum Dots ‘QD’ in the presence of a magnetic field is theoretically investigated. For higher field strength and large dot, the magnetic field effects are predominant. The numerical calculations are performed in the effective mass approximation, using a variational method. We describe the effect of the quantum confinement by an infinite deep potential. The form effect is studied for the Spherical Quantum Dot ‘SQD’ and Cylindrical Quantum Dot ‘CQD’. The results for these two forms of structures show that the diamagnetic susceptibility and the binding energy increase with the magnetic field. There are more pronounced for larger dot. We remark that for a zero magnetic field, the binding energy and the diamagnetic susceptibility are decreasing functions of the quantum dot dimension and compared with theoretical results in literature. We hope that this work will stimulate further experimental activity on donors in quantum dot structures.